Online Project-Based Learning (O-PjBL): Effectiveness in Teachers Training and Coaching in Vocational Education - Sudira, Putu; Nurtanto, Muhammad; Masrifah, Nani; Nurdianah, Evi; Mutohhari, Farid (Universitas Pendidikan Ganesha, 2022)
Vocational teachers need effective and interactive classroom management during online learning. This study aims to describe the concept of training, measure the perception of vocational teachers, and measure effectiveness during training and coaching of vocational teachers in online learning using project-based learning (O-PJBL). This study applies a combined evaluative method with the Plan-DO-Check-Evaluation (PDCA) stage to explore the concept of training and coaching, then test the perception and effectiveness of applying the quasi-experimental method. A total of 70 vocational teachers were involved in the study. Data were collected using observation sheets, online questionnaires with a scale of 1-4, and pretest-posttest questions. The data were analyzed based on the activities of vocational teachers and inferential statistical analysis. The results of the research are (1) the implementation of vocational teacher training and development with the PDCE approach resulting in project-based online learning based on the characteristics of the subject; (2) the perception of vocational teachers on aspects of content relevance, content suitability, presentation quality, content mastery, and time allocation is very good with a significance value based on gender is 0.892, employment status is 0.456, and age range is 0.142; and (3) there was a positive increase in the understanding of the material and the quality of learning tools. The quality of future vocational learning is determined by teachers who are up to date with changes.